STRATEGI PEMBELAJARAN UNTUK ANAK USIA DINI - Nuraeni Nuraeni (IKIP Mataram, 2014)
Learning strategy is needed for optimal learning process according to planning. Educators have an enormous influence on the growth and development of children's intelligence. The principles of early childhood learning are goal-oriented, activity, individuality, integrity, interactive, inspirational, fun, challenging, motivational. Student-centered learning approach models are: Montesori approach model, Street bank approach model, High Scope approach model, Creative curriculum approach model, Emillia Region approach model